Microelectrode arrays for electrochemistry: approaches to fabrication. - Huang, X; O'Mahony, A; Compton, R (2009)
Microelectrode arrays have unique electrochemical properties such as small capacitive-charging currents, reduced iR drop, and steady-state diffusion currents. These properties enable the use of microelectrode arrays and have captured much interest in the field of electrochemistry. Techniques for the fabrication of such arrays are reviewed. The relative features and merits of different techniques are also discussed.